Ecological Colonialism and Local Resistance: A Genealogy of Power in the Style of Foucault and Sean McDonagh's Ecotheology in West Kalimantan - Dismas Kwirinus; Robertus Wijanarko; Pius Pandor; Fransiskus Emanuel (Riviera Publishing, 2025)
This study explores the dynamics of ecological colonialism in West Kalimantan through the intersecting lenses of Michel Foucault's genealogy of power and Sean McDonagh's ecotheological discourse. Drawing upon a critical-theoretical framework, the research investigates how historical and contemporary environmental domination, often justified through state-corporate development narratives, constitutes a form of colonial violence against both nature and indigenous epistemologies. By employing Foucault's concept of power relations and discursive formations, the study deconstructs the mechanisms through which ecological control is normalized, particularly in extractive economies such as palm oil and mining. Simultaneously, McDonagh’s ecotheology offers a normative theological response that reframes the relationship between humanity, creation, and justice, providing a counter-narrative rooted in ecological ethics. The local resistance of communities in West Kalimantan is examined as a site of epistemic contestation, where indigenous cosmologies and spiritualities challenge dominant ecological paradigms. This research contributes to the broader discourse on political ecology, postcolonial theology, and environmental justice by bridging critical theory and contextual theology. It underscores the need to rethink environmental governance through plural epistemologies that honor both ecological integrity and sociocultural sovereignty.